Maritza Montero Rivas: Life and work - Montero López, Víctor (2015)
It presents the various works of Maritza Montero, Venezuelan psychologist, his contributions to Social Psychology, Politics, Community, issues such as national identity, participation, methodology, Liberation Psychology, motivation. Noted its importance and influence in Latin America.